(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The paper deals with the 3D virtual prototyping of garments since they represent an important tool for booth textile and garment designers. It offers simple introduction of changes while developing a model in comparison to conventional techniques, quick response to the costumer's demands and wishes regardless of their location. Moreover, 3D virtual prototyping of garments can successfully replace prototyping processes when the specific garments are designed e.g. garments for people with the non-standard body figure, wheelchair users, sportswear etc. The advantages and disadvantages of virtual prototyping of garments, used processes and methods, as well as the suggestions for new research opportunities on the field of virtual simulation of garments and textile materials are presented.